ON THE INTERNAL NATURE OF KNOWLEDGE AND THE IMPOSSIBILITY OF SCEPTICISM - González Estrada, Allan (2007)
Representationalism has been the philosophical mainstream approach to the metaphysical problem of consciousness, at least in the last three decades. Under this view, the explanation of consciousness in physical, intentional and external terms is possible while the brain itself is excluded as the source of consciousness experience. However, this account is highly problematic. I offer another view, based on an internalistic approach of experience via a non-reductive physicalism, that explain that it is the best path to explain the nature of our phenomenal consciousness and intentionality. This view while avoid the problem of scepticism is a straightforward explanation of the whole metaphysical and epistemological nature of the reality.